A Production and operations management study on JTA Packaging Company - Camacho, Rowena Grace D.; Malig, Mary Magdalene; Razon, Pocholo B. (Diliman, Quezon City College of Engineering, 2001)
JTA Packaging is a single proprietorship company that produces different kinds of packaging products or polybags. These plastic products come from two main raw materials, namely, polyethylene and polypropylene. Among these types, the study focused only on the production of polyethylene plastics, since these products obtained a higher demand than polypropylene plastics during the year 2000. JTA Packaging markets its products locally to various retail and wholesaler establishments such as Monterey Farms Corporation, San Miguel Food Corporation, Champan Garment Corporation, etc. The study analyzed JTA Packaging, from its strategic plans to its tactical decisions, and then, more specifically, to its operational planning and control decisions. Various analysis techniques were applied, some of which include capacity planning, systems simulation, layout analysis, and improvement technique, streamline diagnosis diagram analysis, and ishikawa diagram analysis. Furthermore, the researchers probed into its systems and operations, and were able to identify various problems that were present within the said company. Among these, three main problems pervading within the company were identified. These are the following: (1) bottleneck in extrusion, (2) fluctuating reorder quantity, and (3) inaccurate forecasting technique used. Further in depth analysis resulted to the following recommendations: (1) Utilize an additional extruder machine, (2) employ a fixed-order quantity inventory scheme, and (3) apply exponential smoothing method as the company' forecasting technique.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: JTA Packaging Company; Packaging industry; Production engineering